2017
DOI: 10.1016/j.neuropharm.2017.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Valproate increases dopamine transporter expression through histone acetylation and enhanced promoter binding of Nurr1

Abstract: The dopamine transporter (DAT) is the key regulator of dopaminergic transmission and is a target of several xenobiotics, including pesticides and pharmacological agents. Previously, we identified a prominent role for histone deacetylases in the regulation of DAT expression. Here, we utilized a rat dopaminergic cell line (N27) to probe the responsiveness of DAT mRNA expression to inhibitors of histone acetylation. Inhibition of histone deacetylases (HDACs) by valproate, butyrate and Trichostatin A led to a 3 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 68 publications
2
21
0
Order By: Relevance
“…Using HDAC inhibitors, Green et al. () observed increases of DAT mRNA expression in rat N27 mesencephalic cells, accompanied by significant increases in Nurr1 and Pitx3 mRNA expression. A detailed description is provided in Table .…”
Section: Mechanisms Underlying the Effects Of Social Defeat Stress Onmentioning
confidence: 99%
“…Using HDAC inhibitors, Green et al. () observed increases of DAT mRNA expression in rat N27 mesencephalic cells, accompanied by significant increases in Nurr1 and Pitx3 mRNA expression. A detailed description is provided in Table .…”
Section: Mechanisms Underlying the Effects Of Social Defeat Stress Onmentioning
confidence: 99%
“…Inhibition of histone deacetylases (HDACs) and glycogen synthase kinase 3 (Gsk3α and β) are the most prominent mechanisms suspected to be involved in the mood-stabilizing effects of VPA [16][17][18][19] .VPA has been demonstrated to be an inhibitor of HDACs both in vitro and in vivo 20,21 . Chromatin remodeling mediated through HDAC inhibition may lead to transcriptional control of target genes related to neuronal differentiation, protection, and the regulation of behavioral dimensions such as mood and cognitive states 16,17,22 .In conclusion, our findings uncovered an effect of chronic VPA treatment on Ncs-1 expression that is mediated through inhibition of Gsk3. These data support a potential contribution of Ncs-1 to the behavioral effects of mood stabilizers and provide a mechanism by which inhibition of Gsk3 affects mood-related behavioral response.…”
mentioning
confidence: 63%
“…Previous studies showed that VPA can increase gene expression through the inhibition of histone deacetylases (HDACs) 22,53,54 , however it is unlikely that VPA mediates Ncs-1 upregulation through this pathway since both in vitro and in vivo treatments with HDAC inhibitors did not induce Ncs-1 expression ( Fig. 2).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Neurotoxicity caused by transcriptional genes (BDNF, GDNE, HSP70, and TH+-IR), α-synuclein and MPP+ is inhibited by using HDAC inhibitors (Harrison and Dexter, 2013). A study of DAT promoter in the cultured rat N27 cell shows a significant role of valproate in regulating DAT expression via elevating the histone acetylation and proves to be neuroprotective (Green et al 2017).…”
Section: Parkinson's Diseasementioning
confidence: 99%